Anterior glottoplasty: the effect of inclusion of the vocal fold lamina propria to frequency elevation. (2nd January 2022) - Yu, Pengcheng; Fang, Rui; Xue, Chao; Jiang, Jack
Abstract: Background: Anterior glottoplasty is a commonly used treatment for voice feminization. But it remains in dispute over whether to suture of the ligament as part of the procedure. Objectives: This study aimed to explore the effect of inclusion of the vocal lamina propia. Material and methods: Anterior webs were created in 8 excised canine larynges by sutures placed at 10%, 20%, and 30% of the vocal fold length, respectively. The suture depth was divided into two groups: epithelium layer (Shallow Suture, SS group) and deep layers of vocal fold lamina propia (Deep Suture, DS group). Results: For anterior webs between 0% and 30%, the frequency elevation ranged from 3% to 151% of the pre-web fundamental frequency (fo) in SS group and from 13% to 222% in DS group. No significance was found between two groups at three different sutures ( p  = .486 for suture at 10% of vocal fold length, 0.686 for 20%, 0.886 for 30%, respectively). Conclusions and significance: The frequency in excised canine larynx increased continuously as the anterior glottic webs ranged from 0% to 30%. The inclusion of the vocal fold lamina propia does not affect the frequency elevation.